Oceanography of the New Zealand subantarctic region - Forcén-Vázquez, Aitana (11699876) (2015)
Subantarctic New Zealand is an oceanographycally dynamic region with the Subtropical Front (STF) to the north and the Subantarctic Front (SAF) to the south. This thesis investigates the ocean structure of the Campbell Plateau and the surrounding New Zealand subantarctic, including the spatial, seasonal, interannual and longer term variability over the ocean properties, and their connection to atmospheric variability using a combination of in-situ oceanographic measurements and remote sensing data. The spatial and seasonal oceanographic structure in the New Zealand subantarctic region was investigated by analysing ten high resolution Conductivity Temperature and Depth (CTD) datasets, sampled during oceanographic cruises from May 1998 to February 2013. Position of fronts, water mass structure and changes over the seasons show a complex structure around the Campbell Plateau combining the influence of subtropical and subantarctic waters. The spatial and interannual variability on the Campbell Plateau was described by analysing approximately 70 low resolution CTD profiles collected each year in December between 2002 and 2009. Conservative temperature and absolute salinity profiles reveal high variability in the upper 200m of the water column and a homogeneous water column from 200 to 600m depth. Temperature variability of about 0.7 °C, on occasions between consecutive years, is observed down to 900m depth. The presence of Subantarctic Mode Water (SAMW) on the Campbell Plateau is confirmed and Antarctic Intermediate Water (AAIW) reported for the first time in the deeper regions around the edges of the plateau. Long-term trends and variability over the Campbell Plateau were investigated by analysing satellite derived Sea Level Anomalies (SLA) and Sea Surface Temperature (SST) time series. Links to large scale atmospheric processes are also explored through correlation with the Southern Oscillation Index (SOI) and Southern Annular Mode (SAM). SST shows a strong seasonality and interannual variability which is linked to local winds, but no significant trend is found. The SLA over the Campbell Plateau has increased at a rate of 5.2 cm decade⁻¹ in the last two decades. The strong positive trend in SLA appears to be a combination of the response of the ocean to wind stress curl (Ekman pumping), thermal expansion and ocean mass redistribution via advection amongst others. These results suggest that the variability on the Campbell Plateau is influenced by the interaction of the STF and the SAF. The STF influence reaches the limit of the SAF over the western Campbell Plateau and the SAF influence extends all around the plateau. Results also suggest different connections between the plateau with the surrounding oceans, e.g., along the northern edge with the Bounty Trough and via the southwest edge with the SAF. A significant correlation with SOI and little correlation with SAM suggest a stronger response to tropically driven processes in the long-term variability on the Campbell Plateau. The results of this thesis provide a new definitive assessment of the circulation, water masses and variability of the Campbell Plateau on mean, annual, and interannual time scales which will support research in other disciplines such as palaeoceanography, fisheries management and climate.